Giant Cell Arteritis of the Superior Mesenteric Artery Presenting With Wernicke Encephalopathy From Thiamine Deficiency. (5th December 2022) - Shapiro, Sarah; Renner, David; Farese, Ludovica
Abstract : Objective: N/A. Background: Giant cell arteritis (GCA) is one of the most common systemic vasculitides in adults over the age of 50 with incidence ranging from 15 to 35 per 100, 000 individuals. The disorder is often included in the differential diagnosis of maladies producing atypical facial pain, headache, visual loss, amaurosis fugax, jaw pain, elevated inflammatory markers, and anemia. GCA is typically known to affect cranial arteries with physical exam findings of tenderness to palpation of the temporal arteries and cranial neuropathies. Clinical diagnosis is further supported by new headache, temporal artery abnormality, elevated ESR (= 50 mm/h), and abnormal artery biopsy. Design/Methods: N/A. Results: A 68-year-old female with history of primary generalized seizures presented to clinic with a 6-week history of paroxysms of acute confusional episodes, the inability to arise from a seated position due to lower extremity weakness bilaterally, alterations of consciousness without loss of consciousness, severe anorexia, and weight loss. MRI with contrast including Axial FLAIR/T2/Diffusion revealed bilateral pan-lobar cortical and subcortical atrophy with ex-vacuo ventriculomegaly and mild leukoaraiosis in the subcortical white matter tracts. PET-CT body revealed linear uptake involving the aortic root, extending into subclavian arteries bilaterally with segmental involvement of proximal common carotids, and extending inferiorly to the level of the common iliac arteries and the mesenteric arteries. Temporal artery biopsy revealed presence of granulomas with multinucleated giant cells. Serology panel revealed pan hypovitaminoses in Vitamins A, B1, B6, B12, and D. Conclusions: Traditional GCA workup initially resulted inconclusive for the patient, whose condition deteriorated as the patient's altered mental status and dizziness spells continued unremittingly. This case highlights the link between large vessel vasculitis and malabsorption syndromes, with the involvement of the superior mesenteric artery, a medium sized vessel, in GCA previously unrecognized. Furthermore, this case is a superb example of multiple etiologies of treatable causes of reversible dementia.